Revealing Amur tiger family pedigrees based on age identification using fecal microbiome and kinship analysis - Hu, Xiaoyun; He, Zhijian; Liu, Chang; Zhang, Yifei; Mu, Dejun; Guskov, Valentin Yu; Wang, Kai; Yao, Yong; Jin, Dan; Lu, Junguang; Ning, Yao; Jiang, Guangshun (Frontiers in Microbiology, 2025)
IntroductionThe construction of a species’ family pedigree is crucial for understanding population structure, assessing genetic diversity, and conserving the genetic resources of endangered species. However, developing non-invasive and reliable methods for age identification in wild individuals remains a significant challenge in family pedigree establishments.MethodsIn this study, we employed 16S rRNA sequencing and metagenomic analysis to examine 30 fecal samples collected from captive Amur tigers across three distinct age groups, aiming to identify the age-specific biomarker, which could subsequently facilitate age determination of wild individuals and support the construction of species pedigree.ResultsOur results demonstrate that, through 16S rRNA high-throughput sequencing, 16 potential microbial age biomarkers were identified in fecal samples from captive Amur tigers, and the ages of 17 captive individuals were distinguished. Notably, f_Erysipelotrichaceae_Unclassified and Paraclostridium, identified as potential age-associated bacterial markers in captive Amur tigers, were also detected in fecal samples from wild individuals of this species. To explore their potential application in age inference for Amur tigers, we integrated genetic relationship analysis with these potential age-specific biomarkers to construct a comprehensive pedigree of wild Amur tigers.DiscussionThis study established a comprehensive scientific framework for pedigree reconstruction based on age determination in Amur tigers and developed a scalable, non-invasive methodology offering opportunities for population structure and promoting the precision of conservation for wild tigers.